2004
DOI: 10.1271/bbb.68.2346
|View full text |Cite
|
Sign up to set email alerts
|

Localization of α-Glucosidases I, II, and III in Organs of European Honeybees,Apis melliferaL., and the Origin of α-Glucosidase in Honey

Abstract: Three kinds of alpha-glucosidases, I, II, and III, were purified from European honeybees, Apis mellifera L. In addition, an alpha-glucosidase was also purified from honey. Some properties, including the substrate specificity of honey alpha-glucosidase, were almost the same as those of alpha-glucosidase III. Specific antisera against the alpha-glucosidases were prepared to examine the localization of alpha-glucosidases in the organs of honeybees. It was immunologically confirmed for the first time that alpha-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 10 publications
1
53
0
Order By: Relevance
“…We purified an -glucosidase from honey. 10) The properties of honey enzyme coincided completely with WHGase III, indicating a significant physiological role of WHGase III in the honey-formation process. WHGase III, secreted from hypopharyngeal gland to the nectar gathered by honeybees, was responsible for converting sucrose (main carbohydrate in nectar) to glucose and fructose (main components in honey).…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…We purified an -glucosidase from honey. 10) The properties of honey enzyme coincided completely with WHGase III, indicating a significant physiological role of WHGase III in the honey-formation process. WHGase III, secreted from hypopharyngeal gland to the nectar gathered by honeybees, was responsible for converting sucrose (main carbohydrate in nectar) to glucose and fructose (main components in honey).…”
mentioning
confidence: 73%
“…5,6) Three -glucosidases were different in molecular size, pH-stability, temperature-stability, substrate specificity, and localization in organ. [5][6][7][8][9][10] They were glycoproteins containing sugar content of 25% (WHGase I), 15% (WHGase II), and 7.4% (WHGase III), which might y To whom correspondence should be addressed. Tel/Fax: +81-11-706-2808; E-mail: kimura@abs.agr.hokudai.ac.jp Abbreviations: DP, average degree of polymerization of glucose; GH, glycoside hydrolase family; JHGase I, Japanese honeybee -glucosidase isoenzyme I; PAGE, polyacrylamide gel electrophoresis; pNPG, p-nitrophenyl -glucoside; RACE, rapid amplification of cDNA end; WHGase I, WHGase II, and WHGase III, western honeybee -glucosidase isoenzyme I, II, and III, respectively affect solubility in ammonium sulfate separation of the purification procedure.…”
mentioning
confidence: 99%
“…Pro226-Tyr227 of HBG-III and their equivalents are indicated by bold-faced letters. The partial sequences, listed from the top, are of -glucosidase isozymes III, II, and I from Apis mellifera (HBG-III, HBG-II, and HBG-I respectively), 6,12) Taka-amylase from Aspergillus oryzae, 25) Bacillus subtilisamylase, 26) sucrose hydrolase SUH from Xanthomonas axonopodis, 27) sucrose phosphorylase from Bifidobacterium adolescentis, 28) amylosucrase from Neisseria polysaccharea, 30) trehalulose synthase (MutB) from Psuedomonas mesoacidophila, 31) and dextran glucosidase (SmDG) from Streptococcus mutans. 29) hydrolysate (6 N HCl at 110 C for 24 h) by the ninhydrin colorimetric method using an amino acid analyzer (AminoTac JLC/500V, JEOL, Tokyo).…”
Section: Methodsmentioning
confidence: 99%
“…HBG-III is secreted from the hypopharyngeal grand into the nectar and is involved in honey formation. 6) These enzymes are clearly different in substrate specificity, ability to catalyze transglucosylation, and regioselectivity in transglucosylation. HBG-I shows little or no activity toward nigerose, isomaltose, or soluble starch.…”
mentioning
confidence: 99%
“…Three kinds of glucosidases were purified from honey bees. It was immunologically confirmed that -glucosidase I is present in the ventriculus, -glucosidase II is present in the ventriculus and the haemolymph, and -glucosidase III is present in the hypopharyngeal gland, the latter enzyme being identical with the -glucosidase present in honey (Kubota et al, 2004). The physiological function of -glucosidase II is not yet known.…”
Section: Developmental-specific Expression Of Haemolymph Proteins In mentioning
confidence: 95%